Studi Dasar Pengolahan Minuman Fermentasi: Karakteristik, Pengetahuan dan Perilaku Konsumennya - Rasmikayati, Elly; Suminartika, Eti; Saefudin, Bobby Rachmat (Universitas Galuh, 2025)
Fermented drinks made from fruits and spices are known to be beneficial for health and have high economic value. Public interest in these types of drinks has increased. However, the level of public knowledge and consumption of fermented drinks is still very low. The purpose of this study was to identify the relationship between the characteristics of fermented drink consumers with consumer knowledge and consumption behavior. The research method used a survey method. The characteristics of fermented drink consumers are mostly female, living in boarding houses with flu as a common disease. There is a significant relationship between the gender of fermented drink consumers with knowledge about the types and benefits of fermented drinks. Then, the type of fermented drink is significantly related to the type of disease that is often suffered.